Estimating Progress of Execution for SQL Queries - Chaudhuri, Surajit; Narasayya, Vivek; Ramamurthy, Ravi (SIGMOD, 2004)
Today’s database systems provide little feedback to the user/DBA on how much of a SQL query’s execution has been completed. For long running queries, such feedback can be very useful, for example, to help decide whether the query should be terminated or allowed to run to completion. Although the above requirement is easy to express, developing a robust indicator of progress for query execution is challenging. In this paper, we study the above problem and present techniques that can form the basis for effective progress estimation. The results of experimentally validating our techniques in Microsoft SQL Server are promising.